A multiple case study on the contradictory nature between the interior design of selected speakeasy bars in Metro Manila and their compliance to the fire code of the Philippines - Co, Patricia Faustine; Gallardo, Mildred M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Throughout history, a number of cases of casualties from fire in drinking establishments have been reported due to inferior fire safety provisions and evacuation plans. This study examined the means of egress in selected speakeasy bars in Metro Manila in terms of their compliance or non-compliance with Section 10.2.5 (Means of Egress) under the Fire Code of the Philippines (RA 9514). With the recent rise of the speakeasy trend in the local scene, design strategies that may compromise a safe means of egress in these interiors must be delved in to. In line with this, the Theory of Cognitive Dissonance, supported by visual semiotics and the Stroop effect, was used to tackle these issues. Through a purposive sampling method, three speakeasy bars selected in accordance to: location in different cities of Metro Manila, with a business permit, had hidden or disguised entrances, and had an underlying theme or design concept. Instrumentation consisted of a spatial assessment tool for observation, interviews with one staff and two customer respondents for each sample, and consultation with a key informant. Collected data were, then, compared to the aforementioned section of the fire code. Despite speakeasy bars being finally accepted as legal operations today, findings revealed that adapting certain aspects of its original nature still resulted to problematic designs. Furthermore, Filipino culture and customs contributed to issues, as more functions had to be taken into consideration. A number of staff and customer respondents also displayed inadequate level of awareness towards fire emergency situations in such spaces. In conclusion, the incorporation of the context of speakeasy bars in the mainstream and contemporary social scene still needs to be reviewed in terms of their full compliance with the code and existence of unsafe means of egress. Attention is also needed to strengthen the implementation of the Fire Code of the Philippines to ensure public safety.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Bars (Drinking establishments) -- Philippines -- Fires and fire prevention; Bars (Drinking establishments) -- Philippines -- Designs and plans; Building laws -- Philippines; Interior decoration -- Philippines